2021
DOI: 10.1007/s41062-021-00695-7
|View full text |Cite
|
Sign up to set email alerts
|

Utilization phosphogypsum as a construction material for road base: a case study in Vietnam

Abstract: Phosphogypsum (PG) is a by-product of the production of fertilizers from phosphate ores, and it contains some harmful substances to the environment. Thus, it is necessary to stabilize/solidify pollutants when using PG as a filling material. The purpose of this study is to investigate and verify the use of PG as a filling material for a road base through laboratory tests for a case study in Vietnam. In this study, PG incorporated with fly ash was stabilized with cement and lime. The specimens of these mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 42 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…This surpasses the strength of traditionally stabilized inorganic PG materials at the 7-day In comparison, Meskini et al [32] utilized fly ash and lime to stabilize PG roadbed material, achieving strengths below 1 MPa at 7 days and ranging from 1-3 MPa at 30 days. In Ngo et al's study [33], the strength of the cement: PG = 10:90 mixture was less than 1 MPa at day 7 and remained less than 2 MPa at day 28. Shen et al's research [34] reported curing strengths of 2 MPa at 7 days and 8 MPa at 28 days for slag-fly ash-PG solidified material.…”
Section: Effect Of Curing Agent Dosagementioning
confidence: 87%
See 1 more Smart Citation
“…This surpasses the strength of traditionally stabilized inorganic PG materials at the 7-day In comparison, Meskini et al [32] utilized fly ash and lime to stabilize PG roadbed material, achieving strengths below 1 MPa at 7 days and ranging from 1-3 MPa at 30 days. In Ngo et al's study [33], the strength of the cement: PG = 10:90 mixture was less than 1 MPa at day 7 and remained less than 2 MPa at day 28. Shen et al's research [34] reported curing strengths of 2 MPa at 7 days and 8 MPa at 28 days for slag-fly ash-PG solidified material.…”
Section: Effect Of Curing Agent Dosagementioning
confidence: 87%
“…Meskini et al [32] found that the incorporation of fly ash and lime can increase the unconfined compressive strength and enhance durability of the PG composite due to the formation of ettringite as the main hydration product responsible for strength development. Ngo et al [33] demonstrated that the stabilization of a PG and fly ash mixture, along with curing using cement and lime, leads to improved mechanical properties of PG. This approach confirms the practical feasibility of employing PG as a filling material for road base construction.…”
Section: Introductionmentioning
confidence: 99%
“…Japan sets a good example as it reuses 100.0% of its phosphogypsum: 60.0% as gypsum materials in the building industry, 30.0% as a cement retarder, and 10.0% as materials for the medical and food industries . Although phosphogypsum has been widely used in construction, such as cement retarder, , building materials like construction plaster and plastering mortar, and road paving materials, the size of the phosphoric industry and transportation costs have limited its reuse, with a global average reuse rate below 40.0% . , Therefore, innovative and reliable utilization strategies are essential to balance use and production and to maintain a sustainable development of phosphoric industry.…”
Section: Introductionmentioning
confidence: 99%
“…Some harmful gases, such as chlorine fluoride, will enter the atmosphere. After being washed by rain, the soluble impurities in phosphogypsum will dissolve in rain and enter the soil, and then enter the surface water and groundwater through the soil [15]. At present, there are some environmental problems around phosphogypsum storage yard, such as poor water quality, abnormal toxic gas content in the atmosphere, excessive heavy metals in the soil, which seriously endanger the living environment of human beings.…”
Section: Introductionmentioning
confidence: 99%